Main results of the first Brazilian Registry of Heart Failure (BREATHE). (3rd October 2022) - Albuquerque, D C; Barros E Silva, P G; Lopes, R D; Hoffmann, C; Nogueira, P R; Reis, H; Nishijuka, F A; De Figueiredo Neto, J A; De Souza Neto, J D; Rohde, L E P; Simoes, M V; Rocha, R M; et al.
Abstract: Background: Heart failure represents a common cause of hospitalization associated with poor short-term clinical outcomes. Little is known about the long-term prognosis of these patients in Latin America. Methods: The rationale and design of the study were previously published (1). Briefly, BREATHE was the first nation-wide prospective observational study that included patients hospitalized due to acute heart failure in Brazil. In-hospital management as well as 12-month clinical outcomes were assessed. Patients were included during two time periods: from February 2011 to December 2012 (BREATHE I) and from June 2016 to July 2018 (BREATHE Extension). Adherence to evidence-based therapies was also evaluated. Results: A total of 3, 013 patients were included in 71 centers in Brazil. The median follow-up was 346 days. The BREATHE population included 39.3% of women, had a mean age of 65.2 (± 15.6) with a mean ejection fraction of 39.7% (± 17.5). Among the comorbidities, systemic arterial hypertension was the most common, present in almost 75% of the sample. At hospital admission, 83.8% of patients had clear signs of pulmonary congestion and the main cause of decompensation was poor adherence to heart failure medications, representing 27.8% of cases. Among patients with reduced ejection fraction, the concomitant use of renin-angiotensin-aldosterone inhibitors, beta-blocker and spironolactone at hospital discharge was 44.5% and decreased to 35.2% after 3 months (p<0.01). Mortality rate at 12 months was 28.9 for every 100 patient years with 26.2% readmission at 90 days and 46.4% at 365 days. The most common etiology of heart failure was ischemic disease (Figure 1) but the worst prognosis was associated with Chagas disease (Figure 2) including an analysis of a composite outcome encompassing death, myocardial infarction, stroke or cardiac arrest after discharge. Conclusions: In this large national prospective registry of patients hospitalized with acute heart failure, mortality and readmission were higher than what have been reported globally. Poor adherence to evidence-based therapies was a common both at hospital discharge and 1-year of follow-up. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Brazilian Society of Cardiology